SIMULASI INTERKONEKSI ANTARA AUTONOMOUS SYSTEM (AS) MENGGUNAKAN BORDER GATEWAY PROTOCOL (BGP) - Hari Antoni Musril (InfoTekJar : Jurnal Nasional Informatika dan Teknologi Jaringan, 2017)
An autonomous system (AS) is the collection of networks having the same set of routing policies. Each AS has administrative control to its own inter-domain routing policy. Computer networks consisting of a bunch of AS's with different routing will not be able to interconnecttion one another. This is causes communication in the network to be inhibited. For that we need a protocol that can connect each different AS. Border Gateway Protocol (BGP) is an inter-domain routing protocol i.e. between different AS  that is used to exchange routing information between them. In a typical inter-network (and in the Internet) each autonomous system designates one or more routers that run BGP software. BGP routers in each AS are linked to those in one or more other AS. The ability to exchange table routing information between Autonomous System (AS) is one of the advantages BGP. BGP implements routing policies based a set of attributes accompanying each route used to pick the “shortest” path across multiple ASs, along with one or more routing policies. BGP uses an algorithm which cannot be classified as a pure "Distance Vector", or pure "Link State". It is a path vector routing protocol as it defines a route as a collection of a number of AS that is passes through from source AS to destination AS. This paper discusses the implementation of the BGP routing protocol in the network that have different AS in order to interconnect. Its application using Packet Tracer 7.0 software for prototyping and simulating network. So that later can be applied to the actual network. Based on experiments that have been carried out, the BGP routing protocol can connect two routers that have different autonomous system.